OVARIAN STEROIDAL PROFILE AND FERTILITY TO INSULIN AND GnRH ADMINISTRATION IN POSTPARTUM ANESTRUS BUFFALOES
To study the effect of exogenous administration of insulin on ovarian and fertility response in anestrus buffaloes, 18 true anestrus buffaloes were selected and equally divided into 3- groups (n=6). Animals of group-I (G1) received subcutaneous injection of highly purified long acting bovine insulin at the dose of 0.25 I U kg-1 bodyweight, once daily for 5 consecutive days. Animals of group II (G2) received an intramuscular injection of 20 μg buserelin acetate where as animals of group-Ill (control) received an intramuscular injection of 2.5 ml sterile saline. In response to the treatment, 50 and 33.33% animals were induced in estrus with in 25 ± 0.94 and 9.5±3.18 days from start of treatment, respectively in G1 and G2; however, no animal was induced in estrus in control group. Conception rate at induced estrus was 100% in both the treatment groups. The mean serum progesterone (P 4 ) concentration was less than 1 ng/ml on day before start of treatment, day 71h and 14111 following start of treatment in all the experimental animals. The basal level of P 4 concentration (nglml) at induced estrus (0.44 ±0.25 and 0.19 0.04) increased (4.46 ± 0.22 and 4.4 7 ± 0.58) significantly (p<O. 05) at day 10 post estrus, respectively, in G 1 and G2. No significant difference in serum estradiol-17b(E2